Effects of potassium/sodium fertilization and throughfall exclusion on growth patterns of Eucalyptus grandis W. Hill ex Maiden during extreme drought periods - Chambi-Legoas, Roger (2019)
In Brazil, most Eucalyptus plantations are located in regions experiencing periods of water shortage where fertilizers are intensively used to achieve high productivity. Fertilization can affect water use. However, the effects of fertilization on tree growth patterns during extreme droughts periods remain unknown. A throughfall exclusion experiment was set up in Sao Paulo State-Brazil to study the effects of potassium (K) and sodium (Na) fertilization and their interaction with water supply in the growth of Eucalyptus grandis trees over an abnormal season of 6 months of extreme drought in comparison with that in normal seasons, as well as the differences in responsiveness to intra-annual meteorological variability. Arranged in a split-plot design, the factors were water supply (37% throughfall exclusion vs. no throughfall exclusion) and fertilization regime (K, Na, and control). Basal area growth was monitored by band dendrometers measurements at 14-day intervals over 2 years. Meteorological and soil water content data were also collected. K and Na fertilization increased the tree basal area by four and three-fold, respectively, during normal seasons. During a severe drought season, these positive effects were suppressed. However, K- and Na-fertilized trees achieved a similar cumulative basal area increment to that of the control trees. The 37% throughfall exclusion significantly decreased tree growth in all treatments only in the severe drought period, and these effects were stronger in K-fertilized trees. K-fertilized trees were highly responsive to intra-annual meteorological variability. Our results suggest that extreme drought has similar effects on E. grandis tree growth regardless of the K/Na fertilization regime.